COLLABORATIVE GOVERNANCE IN MARINE ECOTOURISM DEVELOPMENT: NAVIGATING STAKEHOLDER INTERESTS AT RED ISLAND BEACH, INDONESIA - Tito Mariano Yesayabela; Sasmito Jati Utama (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the implementation of collaborative governance in the context of developing marine ecotourism on the Pulau Merah Coast of Banyuwangi Regency, Indonesia. Specifically, it focuses on evaluating the dynamic collaboration processes among stakeholders and identifying the key elements of successful and sustainable ecotourism development through this multi-stakeholder approach. The research employed a qualitative method using a descriptive approach. Primary data was gathered through semi-structured interviews with key informants representing government, private sector, and community groups, as well as via field observations. Secondary data was sourced from relevant documents and reports. The collected data was analyzed using an interpretive process of thematic categorization and comparison. The findings highlight that collaborative governance at Pulau Merah involves complex, non-linear dynamics. Key discussion results indicate that initial drivers like leadership, pre-history of cooperation, and perceived interdependency significantly initiate the collaboration process. However, the study identifies critical bottlenecks within the formal process itself, particularly challenges in maintaining ongoing dialogue among stakeholders with divergent interests, ensuring full commitment to shared goals, and establishing intermediate-term indicators for transparent monitoring. The results emphasize that overcoming these process-oriented challenges is crucial for transitioning from initial collaboration stages to long-term, tangible impacts.